The Power of Proof of Visum Et Repertum as Evidence in Murder Cases: A Case Study of Vina's Murder - Romlahayati, Yanti; Nurhaqi, Ari; Henda, Raden; Ika Putri, Dessy; Nurfaidah, Gina; Noupel, M. Noupel (Jurnal Legisci, 2024)
Murder cases have always increased significantly every year, with an increasingly violent modus operandi. One of the main challenges in uncovering murder cases is the limited evidence that can uncover legal facts. In the investigation process, it is necessary to have at least two valid pieces of evidence, one of which is expert testimony. Expert testimony is usually stated in the Visum et Repertum, which is very important in proving the crime. Visum et Repertum is a forensic medical statement that plays an important role in determining the cause of death, identifying the victim, and estimating the time of death. In terms of the application of Visum et Repertum, mistakes can occur; one of the cases of murder that is going viral today is the Vina murder case that occurred in 2016. In the case of Vina's murder, after going viral, new evidence emerged that was revealed even though there was a court decision with permanent legal force. This study aims to examine the role and position of Visum et Repertum as evidence in proving the crime of murder, with a case study on the case of Vina's murder at the Cirebon City District Court. The method used is a normative juridical approach, with secondary data in the form of court decisions and legal documents. The results of the study show that Visum et Repertum has a significant role in the process of proving the Vina murder case in Cirebon City, although sometimes, there can be errors in interpretation that affect the accuracy of legal decisions. Visum et Repertum provides authentic evidence that is important to solve the legal puzzle in the case of Vina's murder in Cirebon City, so it needs to be carefully considered by the judge in making a decision.